Anti-NXP2 autoantibodies in adult patients with idiopathic inflammatory myopathies: possible association with malignancy. Issue 5 (17th January 2012) - Ichimura, Yuki; Matsushita, Takashi; Hamaguchi, Yasuhito; Kaji, Kenzo; Hasegawa, Minoru; Tanino, Yoshinori; Inokoshi, Yayoi; Kawai, Kazuhiro; Kanekura, Takuro; Habuchi, Maria; Igarashi, Atsuyuki; Sogame, Ryosuke; et al.
Abstract : Objectives: Myositis-specific autoantibodies (MSAs) are useful tools for identifying clinically homogeneous subsets and predicting prognosis of patients with idiopathic inflammatory myopathies (IIM) including polymyositis (PM) and dermatomyositis (DM). Recent studies have shown that anti-NXP2 antibody (Ab) is a major MSA in juvenile dermatomyositis (JDM). In this study the frequencies and clinical associations of anti-NXP2 Ab were evaluated in adult patients with IIM. Methods: Clinical data and serum samples were collected from 507 adult Japanese patients with IIM (445 with DM and 62 with PM). Eleven patients with JDM, 108 with systemic lupus erythematosus, 433 with systemic sclerosis and 124 with idiopathic pulmonary fibrosis were assessed as disease controls. Serum was examined for anti-NXP2 Ab by immunoprecipitation and western blotting using polyclonal anti-NXP2 Ab. Results: Seven patients (1.6%) with adult DM and one (1.6%) with adult PM were positive for anti-NXP2 Ab. Except for two patients with JDM, none of the disease controls were positive for this autoantibody. Among eight adult patients with IIM, three had internal malignancies within 3 years of diagnosis of IIM. Another patient with DM also had a metastatic cancer at the diagnosis. All of the carcinomas were at an advanced stage (stage IIIb–IV). Conclusions: While less common than in juvenile IIM, anti-NXP2 Ab was found in adult IIM. Anti-NXP2 Ab may be associated with adult IIM with malignancy.